Changes in paddy soil fertility in Thailand due to the Green Revolution during the last 50 years. Issue 6 (1st November 2020) - Yanai, Junta; Hirose, Mina; Tanaka, Sota; Sakamoto, Keita; Nakao, Atsushi; Dejbhimon, Ketsuda; Sriprachote, Anongnat; Kanyawongha, Porntiva; Lattirasuvan, Thanakorn; Abe, Shin
ABSTRACT: Understanding of the long-term soil fertility trends is the basis for rational and sustainable management of the soil resources in agricultural fields. In tropical Asia, the Green Revolution initiated in the late 1960s contributed to a drastic increase in both food production and human population. Among the tropical Asian countries, Thailand is known as a rice-exporting country, but the country's rice yield is still relatively low. Therefore, this research aimed to investigate the effect of the Green Revolution on the changes in paddy soil fertility status in Thailand over the last 50 years. In total, 65 surface soil samples were collected in 2015 and 2016 from paddy fields in the northeast, north, central plain, and Bangkok Plain of Thailand. To compare the fertility-related data of the samples with those of soils collected from 1964 to 1972, the sampling sites in the 2010s were placed at or near the same locations of the original sites. Over the last 50 years, the mean pH, total C, total N, available N, available P, and exchangeable K values increased significantly (p < 0.01). In particular, the available P content dramatically increased from 3.19 to 42.8 mg kg –1, reflecting the rapid increase in fertilizer application. Contrarily, the mean exchangeable Mg and clay content values decreased significantly (p < 0.05). Regionally, the total C and total N contents of the soils in the northeast were significantly lower than those in the other regions (p < 0.05), and the available P, exchangeable K, and available Si contents were often evaluated as deficient, reflecting the very sandy texture of the soils. In conclusion, the fertility status of the paddy soil in Thailand has improved considerably over the last 50 years, and the increase in total C suggests the potential of paddy soil for C sequestration, even in the tropics. These trends should be considered to achieve more sustainable food production and environmental conservation in Thailand.